2019
DOI: 10.1002/poi3.197
|View full text |Cite
|
Sign up to set email alerts
|

Expressing and Challenging Racist Discourse on Facebook: How Social Media Weaken the “Spiral of Silence” Theory

Abstract: This article examines the discursive practices of Facebook users who use the platform to express racist views. We analyzed 51,991 public comments posted to 119 news stories about race, racism, or ethnicity on the Canadian Broadcasting Corporation News Facebook page. We examined whether users who hold racist viewpoints (the vocal minority) are less likely to express views that go against the majority view for fear of social isolation. According to the “spiral of silence” theory, the vocal minority would presuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…Rather, we can look to users on platforms as another set of informal actors challenging extremist narratives. Drawing on empirical research on thousands of comments on news stories about race, racism, or ethnicity on the Canadian Broadcasting Corporation News Facebook page, Chaudhry and Gruzd (2020) focus on the “spiral of silence” which is a communication theory that “suggests that with increasing social pressure, people may conceal their views when they think their views are in the minority” (Noelle‐Neumann, 1991). Although they suggest that the lack of anonymity on Facebook limits the extent of racist speech observed on the page they study, Chaudhry and Gruzd do find a vocal minority of users participating in racist speech.…”
Section: Strategic Communication Primary Cve and Informal Actorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, we can look to users on platforms as another set of informal actors challenging extremist narratives. Drawing on empirical research on thousands of comments on news stories about race, racism, or ethnicity on the Canadian Broadcasting Corporation News Facebook page, Chaudhry and Gruzd (2020) focus on the “spiral of silence” which is a communication theory that “suggests that with increasing social pressure, people may conceal their views when they think their views are in the minority” (Noelle‐Neumann, 1991). Although they suggest that the lack of anonymity on Facebook limits the extent of racist speech observed on the page they study, Chaudhry and Gruzd do find a vocal minority of users participating in racist speech.…”
Section: Strategic Communication Primary Cve and Informal Actorsmentioning
confidence: 99%
“…Bilazarian's recommendation to focus on networked approaches, interpersonal messaging, and going beyond the narrow frame of counter‐extremism when considering relevant actors in online CVE sets the stage for Benjamin Lee's work on informal counter‐narratives and Irfan Chaudhry and Anatoliy Gruzd's work on comment section racism on Facebook news pages. Where Bilazarian develops policy recommendations that can better guide online‐oriented CVE, Lee (2020) and Chaudhry and Gruzd (2020) provide a granular examination of the challenges facing primary CVE on and through social media.…”
Section: Strategic Communication Primary Cve and Informal Actorsmentioning
confidence: 99%
“…Collectively these studies have revealed how social media platforms create, to varying extent, enclaves within which overt or covert far-right discourses and the sorts of hate-speech underlying them can intensify, while simultaneously providing entry points to broader digitally networked audiences that allow the greater acceptance and normalisation of those same discourses (Farkas and Neumayer, 2017;Merrill and Åkerlund, 2018;Chaudhry and Gruzd, 2020). Social media platforms are thus not just neutral platforms on which racism is expressed, covertly or otherwise.…”
Section: Mediatised Nostalgia Digitised Far-right Discourse and Memementioning
confidence: 99%
“…Fast forward to 2019, social media is now embroiled in a series of ongoing public scandals involving data abuse and misuse-with the most infamous scandal involving the UK data analytics girm Cambridge Analytica. More troubling is the fact that social media has emerged as fertile ground for fostering anti-social behaviour [1], [2] and is an important vector for disinformation, misinformation, information and manipulation operations [3]- [5]. These realities have raised privacy concerns and challenged public trust in social media, which has resulted in a revitalized call for new legislation and regulation [6]- [9].…”
Section: About the Conferencementioning
confidence: 99%